O processo colaborativo de produção de textos orais e escritos: reflexões sobre a interação no ensino-aprendizagem de português língua não-materna - Espindula, Lais (2022)
This paper investigates how the teaching-learning process of Portuguese Non-Native Language through the production of oral and written texts occurs, in the context of a partnership between the extension project Releitores-Ufes and the extension course Português do Brasil- Pré-PEC G. The objective is to understand the role of interaction between students in initial training (monitors), foreign students and other project participants (coordinating teachers and researcher) in the construction of the meanings of the texts and their contributions in the linguistic-discursive formation of those involved, from the collaborative reflections. Theoretically based on the studies of literacies and Bakhtinian dialogism, it is justified by the need to verify the implications of these approaches in the teaching-learning of Portuguese Non-Native Language. It is proposed a qualitative research, of ethnographic and interpretive character, based on the observation (participant) of classes and review services, in the analysis of the initial and final texts (with emphasis on the review and rewriting process), in the reports of the participants through responses to questionnaire and in a field diary produced by the researcher. As a result, it is possible to understand how the subjects involved in the interactive process of teaching-learning a language perceive it and to what extent, through the joint collaborative practices of literacy made possible by the University, the impacts of both the dialogued classes and the collaborative work of reviewing and rewriting the texts in their linguistic-discursive formation are recognized. In addition, the relevance of practices such as those that make it possible to carry out this research is evidenced, considering the specificities of this area that requires a different look at that focused on first language teaching-learning.